Pride and prejudice - Austen, Jane; Jennings, Linda (Puffin Books London, 2018)
When two rich young gentlemen move to town, they don't go unnoticed - especially when Mrs Bennett vows to have one of her five daughters marry into their fortunes. But love, as Jane and Elizabeth Bennett soon discover, is rarely straightforward, and often surprising. It's only a matter of time until their own small worlds are turned upside down and they discover that first impressions can be the most misleading of all